Pengendalian Motor Brushless Direct current Dengan Frekuensi Tinggi Pulse Width Modulation Dengan Metode Back-Electromotive Force Menggunakan Microcontroller - Charles Ronald Harahap; Endah Komalasari (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2023)
Abstract — Research on speed control of electric motors has developed, especially the BLDC motor. In previous research, the pulse width modulation (PWM) has been controlled using the voltage and duty cycle to control the motor speed. The PWM method is a method that is widely used in controlling BLDC motor speed. This research will discuss controlling the speed of the BLDC motor using the PWM modulation method with the switching frequency of 20 KHz and the frequency generated from Arduino reaches 300 Hz. In this study, two tests will be carried out, namely no load and loaded tests. From the two tests carried out, data is obtained in the form of the speed, power, and torque of the motor based on changes in the frequency. The no-load test produces a maximum speed of 14,328 rpm, a power of 71,2 watts, and a torque of 0,047 Nm. During the load test, the maximum speed is 12,060 rpm, power is 79,3 watts, and torque is 0.062 Nm. Keywords— BLDC motor, pulse width modulation, frequency variable, Arduino Mega 2560